2023
DOI: 10.1017/s0272263123000086
|View full text |Cite
|
Sign up to set email alerts
|

Language proficiency modulates listeners’ selective attention to a talker’s mouth: A conceptual replication of Birulés et al. (2020)

Abstract: This study presents a conceptual replication of Birulés et al.’s (2020, Experiment 2) investigation of native and nonnative listeners’ selective attention to a talker’s mouth with the goal of better understanding the potentially modulating role of proficiency in listeners’ reliance on audiovisual speech cues. Listeners’ eye gaze was recorded while watching two short videos. Findings from one of the videos replicated results from the original study, showing greater attention to the talker’s mouth among L2 than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…First, the findings of the current study were limited to Japanese EFL learners without any experience abroad. To examine the generalizability of the findings, they should be replicated with other groups of L2 learners with different levels of immersion experience (Trofimovich & Baker, 2006), L1 backgrounds (e.g., Indo vs. non-Indo-European languages; , L1-L2 (Jaekel et al, 2023), L2 proficiency (Grüter et al, 2023), and aptitude profiles (Linck et al, 2013). Second, many scholars are increasingly conceptualizing L2 listening proficiency as the ability to understand not only L1 speakers but also L2 speakers.…”
Section: Roles Of Phonological Vocabulary In L2 Listening Proficiencymentioning
confidence: 99%
“…First, the findings of the current study were limited to Japanese EFL learners without any experience abroad. To examine the generalizability of the findings, they should be replicated with other groups of L2 learners with different levels of immersion experience (Trofimovich & Baker, 2006), L1 backgrounds (e.g., Indo vs. non-Indo-European languages; , L1-L2 (Jaekel et al, 2023), L2 proficiency (Grüter et al, 2023), and aptitude profiles (Linck et al, 2013). Second, many scholars are increasingly conceptualizing L2 listening proficiency as the ability to understand not only L1 speakers but also L2 speakers.…”
Section: Roles Of Phonological Vocabulary In L2 Listening Proficiencymentioning
confidence: 99%
“…Prior studies have shown that access to such AV redundant speech cues, compared to auditory-only situations, can facilitate lexical access and, more largely, speech comprehension, most notably when the acoustic signal becomes difficult to understand due to noise [ 6 , 7 , 8 , 9 , 10 , 11 ] or to an unfamiliar accent or language (e.g., [ 12 , 13 , 14 ]). In such occasions, adult listeners have been shown to increase their visual attention (hereafter attention) to the talker’s mouth in order to maximize the processing of AV speech cues and enhance their processing of speech; for instance, when background acoustic noise increases [ 15 , 16 ], when volume is low [ 17 ], when their language proficiency is low [ 18 , 19 , 20 ], or when they are performing particularly challenging speech-processing tasks (e.g., speech segmentation [ 21 ] or sentences comparison [ 18 ]). On the other hand, when speech-processing demands are reduced, adults modulate their attention and focus more on the eyes of the talker [ 21 , 22 , 23 ], which can also support language understanding by constraining interpretations (e.g., of the speaker’s current emotion or current focus of attention).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies show that access to such AV redundant speech cues, as compared to auditory-only situations, can facilitate lexical access and more largely speech comprehension, most notably when the acoustic signal becomes difficult to understand, due to noise [6]- [11], or to an unfamiliar accent or language (e.g., [12]- [14]. In such occasions, adult listeners have been shown to increase their attention to the talker's mouth, in order to maximize the processing of AV speech cues and enhance their processing of speech, for instance when background acoustic noise increases [15], [16], when volume is low [17], when their language proficiency is low [18]- [20], or when they are performing particularly challenging speech-processing tasks (e.g., speech segmentation; [21] or sentences comparison; [18].…”
Section: Introductionmentioning
confidence: 99%